Type 2 diabetes in Hulu Selangor: Factors influencing self-care practices from a cross sectional survey / Cassidy Devarajooh - Cassidy, Devarajooh (2018)
The prevalence of diabetes in Malaysia has been increasing from 6.3% in 1986 to 17.5% in 2015. The main aim of diabetes treatment is to achieve optimal glycaemic control, thus preventing or delaying complications. Good diabetes self-care practice is needed to achieve optimal glycemic control. In Malaysia, limited information is available about diabetes self-care practices and its associated factors. This study aimed to identify and determine factors influencing diabetes self-care practices among type 2 diabetics in the district of Hulu Selangor. This was an interviewer administered, cross sectional study, involving 371 randomly selected patients with type 2 diabetes recruited from 6 health clinics in the district of Hulu Selangor, Malaysia. A conceptual model regarding the association between age, sex, education level, diabetes duration, knowledge, social support, empowerment, self-efficacy, depression and diabetes distress with diabetes selfcare practices was developed and analyzed using structural equation modelling. The mean HbA1c level was 8.8 ± 2.3%. Eighteen point one percent had good glycemic control. The mean self-care score was 3.87 ± 0.82. Forty five point eight percent practiced good diabetes self-care. Self-care was not associated with diabetes control. Diabetes self-care practices were similar between sex, age group, ethnicity, and education level. The prevalence of diabetes distress and depression was 5.7% and 4.3% respectively. There was a significant direct positive effect from self-efficacy (path coefficient=0.315, p<0.001) to diabetes self-care. There was a significant direct negative effect from diabetes distress (path coefficient=-0.134, p=0.007) to self-care. Social support had a direct positive effect (path coefficient=0.399, p<0.001) and indirect effect via self-efficacy (path iv coefficient=0.078, p=0.001) on self-care. Though depression had no direct effect on selfcare (path coefficient=0.024, p=0.684), there was an indirect negative effect via selfefficacy (path coefficient=-0.098, p=0.001).In summary, the glycemic control and diabetes self-care practices were poor among the study population. Having higher social support, higher levels of self-efficacy and a lower level of diabetes distress leads to better diabetes self-care practices. Higher levels of social support and being less depressed were associated with better self-efficacy. In conclusion, to improve self-care practices, effort must be focused on enhancing support and self-efficacy levels, while not forgetting to deal with depression and diabetes distress, especially among those with poorer levels of self-efficacy.